microRNAs as therapeutic targets in intestinal diseases - Chen Wang; Jiangning Chen (ExRNA)
Abstract Intestinal diseases, which primarily include inflammatory bowel disease (IBD), colorectal cancer (CRC) and colitis associated cancer (CAC), are believed to develop as a result of heredity transmit, autoimmune disorders, environmental factors and intestinal flora dysbiosis. As small non-coding RNAs, microRNAs (miRNAs) are vital bioactive factors that are important at almost each kind of cellular events. Recent studies have led to novel perceptivity into the roles of miRNAs in the pathogenetic process of many diseases, including intestinal diseases. Thus, miRNAs represent potential goldmines for basic research and therapeutic applications. The present review outlines the research advances of miRNAs in IBD, CRC and CAC, with an emphasis on their application values as therapeutic targets and the associated challenges.